Performance and stability of low temperature transparent thin-film transistors using barrieramorphous multicomponent dielectrics - Barquinha, P.a , Pereira, L.b , Gonçalves, G.a , Martins, R.b , Kuščer, D.c , Kosec, M.c , Fortunato, E.a (Journal of the Electrochemical Society, 2009)
High performance transparent thin-film transistors deposited on glass substrates and entirely processed at a low temperature not exceeding 150°C are presented and analyzed in this paper. Besides being based on an amorphous oxide semiconductor, the main innovation of this work relies on the use of sputtered multicomponent oxides as dielectric materials based on mixtures of Ta2O5 with SiO2 or Al2O3. These multicomponent dielectrics allow to obtain amorphous structures and low leakage currents while preserving a high dielectric constant. This results in transistors with remarkable electrical properties, such as field-effect mobility exceeding 35 cm2 V-1 s-1, close to 0 V turn-on voltage, on/off ratio higher than 106, and a subthreshold slope of 0.24 V decade-1, obtained with a Ta2O5: SiO2 dielectric. When subjected to severe current stress tests, optimized devices show little and reversible variation in their electrical characteristics. The devices presented here have properties comparable to the ones using plasma-enhanced chemical vapor deposited SiO2 at 400°C, reinforcing the success of this amorphous multicomponent dielectric approach for low temperature, high performance, and transparent electronic circuits. © 2009 The Electrochemical Society.
cited By 35